Impact of geopolitical tensions in the red sea on réunion island - Milhiet, Paco (2024)
As geopolitical tensions escalate in the Red Sea, with Houthi rebels targeting numerous vessels in transit, the imperative of maritime security around the Suez Canal, a key chokepoint of global commerce, comes to the fore. Some maritime companies are already rerouting their ships around the southern tip of Africa and the Cape of Good Hope, a prospect carrying potential geopolitical ramifications, particularly for African port cities and islands surrounding the “renewed” southern maritime sea route. Regarding recent events in the Middle East, this article delves into the specific case of Réunion Island, a territory under French sovereignty located in the western Indian Ocean.